Perception of English Learning Based on Local Wisdom for Junior High School Students in Desa Kolam Deli Serdang District North Sumatera Indonesia - Indah Sari; Hanifah Mutia ZN. Amrul (Britain International of Linguistics Arts and Education (BIoLAE) Journal, 2021)
Integrating local wisdom in the context of English learning is very important regarding to the culture maintenance. Learning English as a foreign language has two kinds of motivation namely instrumental and integrative. This study applied qualitative design by administrating the questionnaires to two teachers and 20 students. The results showed that the teachers had not integrated the local wisdom optimally and tended to apply the systemic knowledge in English teaching rather than the schematic knowledge. However, both of them showed their positive responses in relation to integrate the local wisdom in the teaching materials. Furthermore, most students showed their positive responses regarding to integrate local wisdom into English materials in order to maintain and protect their local wisdom and tradition.